The relationship between maternal emotional self-disclosure and children’s anxiety in the post-COVID-19 era - Fatemeh Ghasemi; Fatemeh Valizadeh; Rasool Mohammadi; Hanieh Goodarzi (BMC Psychiatry)
Abstract Background Following pandemics, anxiety often remains prevalent within families, particularly among mothers, even after the acute phase. Mothers typically engage in increased emotional self-disclosure and interactions with family members, which can promote improved mental health and strengthen family dynamics through the shared expression and management of psychological concerns. This study aimed to determine the relationship between maternal emotional self-disclosure and children’s anxiety in the post-COVID-19 era. Methods In this cross-sectional correlation study, 305 mothers of elementary school children in Borujerd, Lorestan, Iran, in 2022 were included using a multi-stage sampling method. Data collection tools comprised demographic questionnaires, the Emotional Self-Disclosure Scale, and the Spence Children’s Anxiety Scale—Parent Report, all of which were completed by mothers as self-reports. Independent t-tests, one-way analysis of variance, Pearson’s correlation test, and multivariate regression were employed to analyze the data. Results There was a negative and significant correlation between mothers’ emotional self-disclosure and children’s anxiety (r = -0.890, P < 0.001) which remained significant after controlling for confounding variables (B = -0.667, P < 0.001). There was a statistically significant difference in mothers’ mean emotional self-disclosure scores based on their place of residence, education, occupation, and their spouse’s age, education, and occupation, as well as the child’s sex, educational level, and age (P < 0.001). However, the results were insignificant concerning the mother’s age (P > 0.05). Conclusions There was an inverse and relatively strong relationship between maternal emotional self-disclosure and child anxiety. This indicates that an increase in maternal emotional self-disclosure was associated with a reduction in child anxiety. Therefore, in similar crises, managing and promoting emotional self-disclosure among mothers may help in reducing children’s anxiety, particularly in mothers who are well-educated, employed, reside in urban areas; have younger, well-educated, and employed spouses; and have female children with younger age and lower educational levels.